Responsive planning in development interventions: consulting rights-holders in the Sanitized Villages programme in Kongo Central. Issue 3 (2nd April 2016) - Destrooper, Tine
ABSTRACT: This article empirically examines one of the most important causes of the non-implementation of human rights-based approaches to development (HRBAD): their alleged limited relevance for actors on the ground. The article argues that claims about local relevance can only be made after meaningful consultation with local rights-holders. Consulting local rights-holders in order to ensure responsive planning is not only relevant for HRBADs, but for development interventions more generally. The article presents new material on the Sanitized Villages programme in the Democratic Republic of the Congo to assess whether and how rights-holders are consulted, and identifies four mechanisms that can facilitate meaningful consultation.